The Analysis of Impedance Spectra for Core–Shell Microstructures: Why a Multiformalism Approach is Essential. (23rd July 2019) - Heath, James P.; Harding, John H.; Sinclair, Derek C.; Dean, Julian S.
Abstract: The impedance response of a core–shell microstructure with 80% core volume fraction has been simulated using finite‐element modeling and compared to two equivalent circuits for a wide range of shell permittivity and conductivity values. Different equivalent circuits, corresponding to different variants of the well‐known brick layer model, are applicable for different combinations of material properties in the microstructure. When the shell has a similar conductivity or permittivity to the core, adding a parallel pathway increases the accuracy of the fit by ≈±10%. When both the conductivity and permittivity values of the core and shell regions are different the series circuit is a better fit. This is confirmed by multiformalism impedance analysis, which reveals features in the data that are not apparent using a single formalism. Finally, the conductivity and permittivity values for both the shell and core are extracted from the simulated spectra using all formalisms and compared to the original input values. The accuracy of the extracted values often depends on the impedance formalism used. It is concluded that impedance spectroscopy data must be analyzed using multiple formalisms when considering core–shell microstructures. Abstract : Impedance spectra of core–shell microstructures of fixed core volume fraction are simulated with finite‐element modeling and analyzed in four formalisms. It is shown that the best formalism to study core–shell impedance spectra varies with shell conductivity and permittivity. The applicability of a brick layer model with a parallel pathway is also evaluated in four formalsims.